English Language Proficiency and Its Relationship with Academic Performance and the Nurse Licensure Examination - Oducado, Ryan Michael Flores; Sotelo, Marianne; Ramirez, Liza Marie; Belo-Delariarte, Rosana Grace; Habaña, Maylin (Nurse Media Journal of Nursing, 2020)
Background: Studies have shown that various factors influence students’ success in nursing school and the Nurse Licensure Examination (NLE). Such factors should be studied as foundations of the nursing programs. Problems with proficiency in the language used by the instructor to teach curricular courses may be considered a barrier to effective learning and academic success.Purpose: This study ascertained the influence of English language proficiency on the academic performance of students in professional nursing courses and the NLE.Methods: This study employed a retrospective descriptive correlational study design. Secondary analysis of existing research data sets of 141 nursing students in one nursing school in the Philippines was performed. Pearson’s r was used to determine the correlation between variables.Results: Findings showed that there were significant correlations between academic performance and the Verbal Ability subscale of the Nursing Aptitude Test (p=0.003) and the three English courses included in the nursing curriculum (p=0.000). There were also significant correlations between the NLE ratings and Verbal Ability (p=0.000) and the three English courses (p=0.000).Conclusion: English language proficiency is an important factor in determining the academic and licensure success of nursing students. Nursing schools must ensure that approaches in improving students' English language proficiency must be well integrated into the undergraduate nursing program.